Correction: Methanobacterium enables high rate electricity-driven autotrophic sulfate reduction. Issue 111 (27th October 2015) - Pozo, Guillermo; Jourdin, Ludovic; Lu, Yang; Ledezma, Pablo; Keller, Jurg; Freguia, Stefano
Abstract : Correction for ' Methanobacterium enables high rate electricity-driven autotrophic sulfate reduction' by Guillermo Pozo et al., RSC Adv., 2015, 5, 89368–89374.